Contribution of foreign germplasm to rice production in China - LI Hai-ming; Hu Rui-fa (浙江大学学报. 农业与生命科学版, 2008)
Genetic contribution of foreign germplasm (particularly those from IRRI and Japan) and their economic impacts on China's rice production were evaluated by analyzing varieties' pedigree information from 25 major rice-producing provinces in China from 1982 to 2002. The results indicated that foreign germplasm resources played important roles in the rice production in China. The yield of rice increased by 21% as the genetic contribution of IRRI germplasm resources increased by 1%; increased by 20% as the contribution of Japan germplasm resources increased by 1%; and increased by 16% as the contribution of other countries germplasm resources increased by 1%. The government should encourage breeders to pay more attention to the use and improvement of foreign germplasm resources.